Las vanguardias artísticas y su deseo: oscilación estética de la contradicción (Dossier: Mímesis desde América Latina) - Terán Ávalos, Daniel Sebastián (2020)
Our understanding of relations and social representations occurs in our recognition of their internal and external articulations and contradictions. An analysis of the artistic vanguards of the XXth century, must thus consider the conjuncture created by modern capitalism’s crisis which sparked its rivalry with the representations of high bourgeios art, in a dispute for reality and low art, under the perception that reality may be transformed in the search for absolute progress and abundance –objects of modern desire–. The literature of Pablo Palacio and Pablo Picasso’s painting illustrate the link between artistic vanguards and modern bourgeois art, in their identification with the same objects of desire and the coexistence of opposites in this historical unity, demonstrating the contradiction of the avant-garde revolution and its modern “utopic spirit”.